Rain attenuation distribution for satellite microwave links application in Tanzania - Promota Haule Linga; Hashim Uledi Iddi; Mussa Kissaka (Institute of Advanced Engineering and Science, 2020)
Rain rate and Rain Attenuation predictions are important in radio system operating at Ku and Ka bands as they affect telecommunication systems performance. To adequately estimate rain-induced attenuation and fading, the International Telecommunication Union (ITU) recommends use of rainfall data collected using 1-minute integration time. For Tanzania, no rainfall data with 1-minute integration time is available either through measurements or conversion from rainfall data with longer integration time. In this paper the rain attenuation is predicted for seven locations in the coastal area of Tanzania. The 1- minute rainfall rate is determined by Chebil’s model using long-term measurements from Tanzania Metrological Agency (TMA) collected for a period of forty years, results obtained are used to estimate rain attenuations. By using the International Telecommunication Union-Recommendation (ITU-R) model, rain attenuation is predicted at horizontal polarization at Ku and Ka band. The results show that Unguja has the highest average annual rainfall accumulation with rain attenuation as high as 53.22dB for Ka band and 15.14dB for Ku band making the difference of about 38.08 between the two frequency bands. On the other hand, Kibaha which has the lowest average annual rainfall accumulation along the coast has rain attenuation of 47.27dB for Ka and 13.41dB for Ku bands, making the difference of 33.86dB between the frequency bands. Results obtained from this study can be useful in designing earth-satellite microwave links in the coastal area of Tanzania.